The Jumonji Domain-Containing Histone Demethylase Homolog 1D/lysine Demethylase 7A (JHDM1D/KDM7A) Is an Epigenetic Activator of RHOJ Transcription in Breast Cancer Cells - Zhang, Ziyu; Chen, Baoyu; Zhu, Yuwen; Zhang, Tianyi; Zhang, Xiaoling; Yuan, Yibiao; Xu, Yong (Frontiers in Cell and Developmental Biology, 2021)
The small GTPase RHOJ is a key regulator of breast cancer metastasis by promoting cell migration and invasion. The prometastatic stimulus TGF-β activates RHOJ transcription via megakaryocytic leukemia 1 (MKL1). The underlying epigenetic mechanism is not clear. Here, we report that MKL1 deficiency led to disrupted assembly of the RNA polymerase II preinitiation complex on the RHOJ promoter in breast cancer cells. This could be partially explained by histone H3K9/H3K27 methylation status. Further analysis confirmed that the H3K9/H3K27 dual demethylase JHDM1D/KDM7A was essential for TGF-β-induced RHOJ transcription in breast cancer cells. MKL1 interacted with and recruited KDM7A to the RHOJ promoter to cooperatively activate RHOJ transcription. KDM7A knockdown attenuated migration and invasion of breast cancer cells in vitro and mitigated the growth and metastasis of breast cancer cells in nude mice. KDM7A expression level, either singularly or in combination with that of RHOJ, could be used to predict prognosis in breast cancer patients. Of interest, KDM7A appeared to be a direct transcriptional target of TGF-β signaling. A SMAD2/SMAD4 complex bound to the KDM7A promoter and mediated TGF-β-induced KDM7A transcription. In conclusion, our data unveil a novel epigenetic mechanism whereby TGF-β regulates the transcription of the prometastatic small GTPase RHOJ. Screening for small-molecule inhibitors of KDM7A may yield effective therapeutic solutions to treat malignant breast cancers.